Synthesis, biological evaluation, and molecular docking study of pyridine clubbed 1,3,4-oxadiazoles as potential antituberculars - Desai, N. C. (Synthetic Communications, 2018)
A series of pyridine clubbed 1,3,4-oxadiazole derivatives were efficiently synthesized, characterized by standard spectral techniques and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG in active and dormant state using an established methods. Compounds 5a, 5m, and 5t were identified as the most active compounds against MTB. Molecular docking was performed against MTB enoyl-ACP (CoA) reductase (FabI/ENR/InhA) enzyme to predict the binding modes and affinity. The theoretical predictions from molecular docking could establish a link between the observed biological activity and the binding affinity shedding light into specific bonded and non-bonded interactions influencing the activity. The active compounds were studied for cytotoxicity against three cell lines and were found to be non-cytotoxic. Specificity of these compounds was checked by screening them for their antibacterial activity against four bacterial strains.
Keywords: antibacterial activity; antituberculosis activity; cytotoxicity activity

Design, synthesis, anti-mycobacterial activity, molecular docking and ADME analysis of spiroquinoxaline-1,2,4-oxadiazoles via [3+2] cycloaddition reaction under ultrasound irradiation - Kanchrana, Madhu; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (MOLECULAR DIVERSITY, 2024)
Keywords: 2; 4-oxadiazoles; cytotoxicity activity; molecular; Mycobacterium tuberculosis; Spiroquinoxaline-1